Orthographic performances in a portuguese primary school: A longitudinal study in third and fourth grades - Martins, Maria Inês de Vasconcelos Braga Horta (2009)
This study aims to understand if children’s spelling errors vary according to their orthographic performances and their grade level. It also aims to understand the way in which children’s awareness of orthography rules relates to their performance. The participants were forty-three children (24 boys and 19 girls) attending the third grade and, the following year, the fourth grade in a Lisbon public school. They were given a spelling task in third grade and again in fourth grade and their spelling errors were compared. In fourth grade, the types of error of good and poor spellers were compared. Interviews were conducted to determine if the level of awareness of orthographic rules differed according to the children’s orthographic performance. The results show that the number of errors decreased from the third to the fourth grade and that there are differences in the types of error made by participants with higher and lower orthographic performances. There were no statistically significant differences between these two groups concerning their awareness of orthographic rules.